Exploring Key Parameters in Adsorption for Effective Fluoride Removal: A Comprehensive Review and Engineering Implications - Letícia Reggiane de Carvalho Costa; Ivone Vanessa Jurado-Davila; Júlia Toffoli De Oliveira; Keila Guerra Pacheco Nunes; Diego Cardoso Estumano; Robson Alves de Oliveira; Elvis Carissimi; Liliana Amaral Féris (Applied Sciences, 2024)
Water pollution, particularly from elevated fluoride ion (F−) concentrations, is a significant challenge in many developing countries, particularly those relying on groundwater. The stable form of fluoride, F−, poses health risks, leading to concerns about various diseases and harmful effects. Despite global efforts, high F− concentrations (>1.5 mg L−1) persist in numerous countries, requiring effective and sustainable removal methods. Adsorption, known for its simplicity, cost-effectiveness, and efficiency, stands out as a promising technique for F− removal from drinking water. Successful commercial implementation necessitates the optimization of separation conditions. This systematic literature review focuses on the adsorption process for F− removal, exploring parameters such as temperature, adsorbent particle size, pH, adsorbent mass, and co-existing ions for efficient removal. Observations indicate that, despite the utilization of a diverse range of adsorbents, several limitations persist. These include low adsorption capacity, a sluggish adsorption rate, a restricted pH range, and high associated costs. The mechanistic understanding of adsorption and the ongoing development of novel adsorbents remain focal points for future research. Additionally, there is a need to explore alternative kinetic models grounded in statistical factors and give due consideration to thermodynamic studies.